CAPITAL STRUCTURE FOR CORPORATE GROWING: CASE HOLDING THE ANDES - Hennings Otoya, Julio Alberto (2014)
This article describes, analyzes and explains the problems of a national corporation growing Andino Investment Holding (AIH), in their quest to realize an efficient capital structure that enables its sustainability going concern, and that allows the further develop-ment achieved in the past decades. The research was based on the review and documentary analysis of eco-nomic and financial information company that works in the Superintendence of Securities Market, the Lima Stock Exchange and reports of risk assessors. Also was tested and reinforced the findings of interviews with officials linked to the case. Finally, observing the direction of the holding, the impossibility of continued growth based on debt, decides to open up capital to outside investors, by the issuance and placement on the Lima Stock Exchange. Previously, AIH and subsidiaries, are forced to make organizational and governance, in line with the new status changes, which will strengthen its development. Resulting from this new capital strategy covered in the capital market, the Holding decreases financial costs and obtains the patrimonial reinforcement consolidate its expansion and economic sustainability.